Measuring the Effectiveness of Environmental Education Programmes in Promoting Sustainable Living in Secondary Schools - Mbokazi, Msawenkosi Sandile; Mkhasibe, Rachel Gugu; Uleanya, Chinaza (Technium Social Sciences Journal, 2021)
Environmental education has been contemplated as the field of study enabling people to live a sustainable livelihood. In recent years, the South African government took an initiative to integrate Environmental Education into all learning areas or subjects. Despite such inclusion, a gap still exists between what is learned in class and what learners are actually doing in their daily activities. Alexander and Poyyamoli, (2014: 1) suggest that Environmental Education is an essential advancement to encourage learners to save, protect and improve the local environment. As a result, the present paper seeks to examine the effectiveness of environmental education programmes in enforcing sustainability behaviours in school children and how it fosters the acquisition of knowledge and understanding, skills, attitude and behaviors compatible to sustainability. The paper employed sustainable indicators as an instrument to evaluation the effectiveness of environmental education programmes in promoting sustainable livelihood. Questionnaires were distributed to teachers, principals and learners from twenty schools in the district. Participants were subjected to pre-test, innovative sustainable living programmes, and post-test assessment. The results of the pre-test portrayed a gap of learners' knowledge, skills and attitude towards their environment, whereas the post-test results confirmed that EE promotes sustainable living when forged with EE programmes.